Synthesis of vertically aligned CaTiO3 nanotubes with simple hydrothermal method and its photoelectrochemical property. (13th July 2018) - Shi, Xiaoguo; Yang, He; Liang, Zhixing; Tian, Ang; Xue, Xiangxin
Abstract: Perovskite-type oxides have become the hotspots of functional materials due to their various excellent performances. As a typical material with a perovskite structure, CaTiO3 (CTO) possesses a similar band gap to TiO2 with less defects and recombination centers, which makes it a promising alternative material to TiO2 . In particular, the CTO nanotube structure has a large specific surface area and unique photochemical and electron-transport properties, and these advantages further expand its application range. In this paper, a highly ordered and vertically aligned CTO nanotube array was successfully synthesized by a simple hydrothermal method with TiO2 nanotube (TNT) arrays as the precursor. It was found that the CTO nanotube had a higher optical absorption ability (3.4 eV), photovoltage (500 mV) and photocurrent density (0.004 A cm −1 ) under ultraviolet irradiation, compared to the TNT (350 mV and 0.0036 A cm −1 ). At the same time, the electrochemical impedance spectroscopy, Mott–Schottky and stability tests indicate that the CTO nanotube might be a promising alternative choice as the photoelectric material for a TNT.